The Influence of Information Technology Usage on Employee Productivity at Perum Damri in Makassar - Gala, Pebrinia; Bandaso, Mira La'bi; Sambara, Kordiana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Study This aiming For analyze influence use technology information to productivity employees at Perum DAMRI Makassar. The method used is approach quantitative with distribution questionnaire to 30 employees as respondents . Data analysis was carried out through Pearson correlation test , the coefficient determination , and t-test. Research results show that there is connection positive and significant between use technology information and productivity employee with mark coefficient correlation of 0.588. The coefficient of determination by 34.6% indicates that use technology information donate influence to productivity employees , while the rest influenced by other outside factors research . The t-test shows t - value (3.849) > t- table (2.048), which strengthens that influence the significant in a way statistics . Findings This show importance implementation technology information optimally for​ increase efficiency work , output quality , and performance employee in a way overall . Therefore that , investment in training digital technology and infrastructure become important strategies for organization For increase productivity source Power man.